Consequences of a Massive Refugee Influx on Firm Performance and Market Structure - Yusuf Emre Akgündüz; Yusuf Kenan Bağır; Seyit Mümin Cilasun; Murat G. Kirdar (Institute of Labor Economics (IZA), 2020)
This study combines an administrative dataset of the full population of Turkish firms and the setting of the sudden mass migration of Syrian refugees to Turkey to identify the effect of migrants on firm performance and market structure. As a result of the migrant shock, existing firms expand and new firms are established. Quantitatively, a 10 percentage-point rise in migrant-to-native ratio increases average firm sales by 4% and the number of registered firms by 5%. While the number of firms rises, new firms are more likely to be small. The resulting market structure shows less concentration and firms reduce the share of workers formally employed. We further document an increased propensity to export and an increase in the variety of exported products. The impact on exports is driven by a rise in competitiveness of firms in regions hosting Syrians as a decline in export prices is observed. We also uncover evidence for an effect of migrants' skills and networks on exports, as the export value and variety of products to the Middle East and North Africa (MENA) region increase more than those to the EU region among exporters while the prices of products exported to the two regions show similar changes.
Keywords: J15; J61; F16; L11; 330; refugees; firm performance; market structure; sales; informality; exports; migrant business networks